Challenges in treating children with optic pathway gliomas: an 18-year experience from a middle-income country - Ramírez-Melo, Jorge Luis; Moreira, Daniel C.; Orozco-Alvarado, Ana Luisa; Sánchez-Zubieta, Fernando; Navarro-Martín del Campo, Regina M. (Frontiers in Oncology, 2024)
Introduction Patients with optic pathway gliomas (OPG) have good survival rates although their long-term quality of life can be affected by the tumor or treatment-related morbidity. This retrospective study sought to describe the clinical presentation and outcomes of children with OPG at a tertiary center in Mexico. Methods Consecutive patients <18 years-of-age with newly diagnosed OPG between January 2002 and December 2020 at the Hospital Civil de Guadalajara Dr. Juan I. Menchaca in Guadalajara, Mexico were included. Results Thirty patients were identified with a median age of six years. The most frequent clinical manifestations were loss of visual acuity (40%) and headaches (23%). Neurofibromatosis-1 was found in 23.3% of the patients. Surgery, either biopsy or resection, was done in 20 of 30 patients. Two patients died shortly after initial surgery. The 5-year event-free survival (EFS) was 79.3% ± 10.8% and the 5-year overall survival was 89.5% ± 6.9%. Lower EFS was associated with age less than 3 years, intracranial hypertension at presentation, and diencephalic syndrome. Patients who received surgery as first-line treatment had a 3.1 times greater risk of achieving a performance score of less than 90 points at 6 months after diagnosis (p=0.006). Of 10 patients with vision testing, 5 had improvement in visual acuity, 4 had no changes, and one patient showed worsening. Conclusion Our data suggests that favorable outcomes can be achieved with OPG in low- and middle-income countries, although a high rate of surgical complications was described leading to a lower overall survival. These data can be used prospectively to optimize treatment at this institute and other middle-income countries through a comprehensive, multidisciplinary approach.